تأثير فيروسY البطاطاPVY)) في بذار بعض أصناف البطاطا المستخدمة محلياً في الزراعة (Latakia University Journal -Biological Sciences Series, 2019)
تم زراعة أربعة أصناف من البطاطا المستخدمة محلياً في الزراعة دراجا, نوفيتا, ليزيتا, فلسينا, بواقع 40 مكرر من كل صنف.   تم التحري عن الإصابة بفيروسات البطاطا Y, X, S, M, A والتفاف الأوراق (PVA ,PVM PVS ,PVX ,PVY ,PLRV) ونسبها في الأصناف الأربعة باستخدام اختبار اليزا الاحتواء المزدوج (DAS-ELISA). وأشارت النتائج إلى وجود فيروس البطاطا Y (PVY) في الأصناف الأربعة المدروسة وبنسب تراوحت ما بين 12.5%في الصنف نوفيتا إلى 31,5% في الصنف دراجا       في حين لم يثبت وجود أيٍ من الفيروسات الأخرى. قدرت نسبة انتقال الفيروس PVY إلى الدرنات الناتجة عن زراعة الدرنات الحاملة للفيروس بإجراء اختبار البصمة النسيجية المناعية (TBIA) على القمم الزهرية المأخوذة من تلك الدرنات.  وثبت أن أعلى نسبة انتقال للفيروس 70.37% في الصنف دراجا وأقلها 44.44% في الصنف ليزيتا. تمّ حساب نسب الإنبات في الدرنات الحاملة لفيروس PVY في الأصناف المختبرة, وجد أن أقل نسبة إنبات كانت34.39 % في الصنف دراجا وأعلاها كانت 80,36 %  في الصنف ليزيتا.   Four potato varieties Draga, Noveta, lizita and Felsena have been planted (40 replicates of each).    Viral infection of potato varieties by potato viruses A, M, S, X, Y and leaf roll (PVA, PVM, PVS, PVX, PVY, PLRV) have been detected  using Double Antibody Sandwich Enzyme-Linked ImmunoSorbent Assay procedure (DAS-ELISA), and infection ratios were estimated. The results showed that; the four  tested potato varieties were infected by PVY, no other viruses were detected, and  the percentage of PVY infection ranges from 12.5% (Noveta variety)  to 37.5% (Draga variety). Transmission ration of PVY to tubers produced from replanting the rose-ends of tubers-born PVY has been estimated using Tissue Blot Immunobinding Assay (TBIA) procedure, the highest PVY transmission ratio was 70.37 % in Draga variety, and the lowest ratio was 44.44 % in Lizita variety. The germination ratio of PVY-born tubers has been calculated in tested potato varieties, the lowest germination ratio was 34.39 % in Draga variety, and the highest  ratio was 80.36 % in Lizita variety.